Sea Stacks: Contemporary Atlantic Canadian Books for Children and Teens - Dixon, Nicole (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This poster describes our SSHRC-funded research project, a web-based resource of Atlantic Canadian authors and books for children and young adults. The resource includes a comprehensive annotated bibliography of primary texts, author and illustrator profiles, and videotaped interviews, and showcases the process of creating the Sea Stacks web resource using Drupal. Cette affiche décrit notre projet de recherche financé par le CRSH : une ressource électronique des auteurs du Canada Atlantique de livres pour enfants et jeunes adultes. Cette ressource comprend une bibliographie annotée exhaustive des principaux textes, le profil des auteurs et des illustrateurs, des entrevues vidéo et illustre le processus de création des ressources Sea Stacks à l’aide de Drupal.